Management Of Childhood Lichen Planus - DM Thapa; M Malathi (Nepal Journal of Dermatology, Venereology & Leprology)
Childhood lichen planus (LP) is a rare entity, with less than 2–3% of all cases seen in patients under 20 years of age. LP in childhood is common in subtropical countries such as India. The most common clinical type of LP in Indian children is the classic form. Approximately 1–15% of patients with LP demonstrate nail involvement, but disease of the nails without skin involvement is rare. LP is diagnosed by historical and physical findings, biopsy results, and, in some cases, features on direct immunofluorescence (DIF). LP tends to have a chronic course. Depending on disease severity, however, LP may respond to a combination of topical or systemic therapies. The response to therapy may be similar to that seen in adults. Moderately potent or super potent steroids are the treatment of choice. Topical steroids can be combined with oral steroids in tapering doses over 2-12 weeks period. This is useful for children with widespread involvement or cutaneous LP lesions associated with significant morbidity. Intralesional steroid is effective for hypertrophic LP unresponsive to topical steroids. Topical steroids in adhesive base used several times a day for several months is a treatment of choice for symptomatic oral LP. Topical steroids in combination with systemic steroids can be given in a tapering dose over 3-6 weeks in very symptomatic cases in early stages. In severe unresponsive cases of both cutaneous and oral LP, oral retnoids are the preferred option. Treatment options for the nail LP in young children are oral steroids given as tapering dose over 4-12 weeks and oral retinoids. Intralesional steroids as nail matrix injection are the third option for older children. Most pediatric patients with LP respond to treatment with full clearance over 1-6 months. Poor response to treatment is a feature of hypertrophic LP and lichen planopilaris.